2009
DOI: 10.1002/dmrr.912
|View full text |Cite
|
Sign up to set email alerts
|

Insulin analogues display IGF‐I‐like mitogenic and anti‐apoptotic activities in cultured cancer cells

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
1
7

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(156 citation statements)
references
References 28 publications
7
141
1
7
Order By: Relevance
“…Biological studies have shown that insulin glargine and insulin detemir have a positive effect on cell cycle progression and display anti-apoptotic activities [14,25]. These results are consistent with our signalling analyses, showing that insulin glargine exhibited IGF-I-like activity in terms of IGF-IR phosphorylation, internalisation and cellular re-distribution.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Biological studies have shown that insulin glargine and insulin detemir have a positive effect on cell cycle progression and display anti-apoptotic activities [14,25]. These results are consistent with our signalling analyses, showing that insulin glargine exhibited IGF-I-like activity in terms of IGF-IR phosphorylation, internalisation and cellular re-distribution.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study, we investigated the biological actions of a series of long-acting and short-acting insulin analogues in cell lines derived from human cancers [14]. The actions evaluated included enhancement of cancer cell proliferation and protection from apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…A pancreatic cancer cell line responded similarly to insulin glargine and human insulin, and survival of insulin glargine-treated patients following treatment for pancreatic cancer did not differ from that of patients on insulin or controls [34]. In another study, colorectal, breast and prostate cell lines showed proliferative changes and increased resistance to apoptosis in response to exposure to pharmacological doses of insulin glargine, insulin detemir and insulin lispro, but not to human insulin [35]. Another recent paper tested the effect of exposure to insulin analogues on a panel of neoplastic and non-neoplastic mammary epithelial cell lines.…”
Section: Insulin Analogues and Cancermentioning
confidence: 94%
“…Ferguson et al (2012) have recently shown that high systemic insulin levels promote breast cancer metastasis in a hyperinsulinemic mouse model by activating c-myc signaling. It has been shown that high-dose human insulin and its analogs promoted T24 (bladder cancer cell), , and PC-3 (prostate cancer cell) proliferation (Weinstein et al 2009, Liu et al 2011b. These reports indicate that metabolic changes occurring in patients with hyperglycemia and hyperinsulinemia lead to increased susceptibility of breast cancer progression.…”
Section: Introductionmentioning
confidence: 98%